Prebivalstveni prag - Jakoš, Aleksander (Urbani izziv, 2002)
The number of births in Slovenia has in the last twenty years almost halved, immigration has stopped and the number of older citizens is increasing while the whole population number is actually decreasing. This phenomenon has been termed ageing population, which is incorrect. In fact it means that there are increasingly more elder citizens, because they reach a higher age, but this isnot the essential problem. A major inconsistency is in the term ageing population itself, by which we want to emphasise the problem of decreasing birth rates and not as a problem of people deceasing later. The condition when the number of births equals the number of deaths is called the demographicthreshold. This problem is extremely pressing in Slovenia because our country is already below the demographic threshold, but not because of ageing. The decreasing number of inhabitants, strong decrease in the number of younger people and also the increasing number of older people, demand new approaches to planning, which cannot be based on imaginary growth, but on quality development. This also applies to cities.
Keywords: demografska struktura; demografski razvoj; human migration; mesta; migracije; prebivalstvo; Slovenia; Slovenija